Rent-seeking en un entorno de alta dependencia de recursos naturales: El caso de Bolivia - Bernardo Fernández; Marcelo Gantier; Martín Palmero (Institute for Advanced Development Studies (INESAD), 2018)
– Between 2006 and 2014, Bolivia experimented an economic boom period driven mainly by high international prices of commodities. Paradoxically, in the same period, social demands increased and concerns related to the high levels of corruption in public administration did not ease, thus suggesting an intensification of a socially undesired behaviour called rent-seeking. This research proposes a general equilibrium modelwhich incorporates a rent-seeking technology whose effects are magnified due to a high dependence on revenues generated from the natural resources sale, aiming to investigate the impact of increasing rent-seeking activities in the economy. The model finds evidence of important loses generated by rent-seeking in Bolivia, not only in terms of output growth but also in terms of welfare.
Keywords: H0; O4; F0; 330; rent-seeking; natural resources; general equilibrium